Sosialisasi Pentingnya Pendidikan Bernilai Dan Peran Orang Tua Dalam Membentuk Karakter Anak Didik Di Sekolah Dasar - Johan Indrus T; Vannisa Avaiana Melinda; Asnawan; Khurin Ratnasari (LP3M IAIFA Kediri, 2025)
Character education for elementary school children is a crucial aspect because elementary school age is included in the golden age, where children have a high ability to absorb life values ​​such as honesty, discipline, responsibility, empathy, and tolerance. Families, especially parents, serve as the first teachers and role models in children's character education, so parental example and interactions at home greatly influence the formation of a child's personality. Although schools also play a crucial role through curriculum and habituation activities, the synergy between schools and parents is often still not optimal, especially in the digital era that brings additional challenges such as the influence of technology and busy parents. This community service uses a Participatory Action Research (PAR) approach to explore and improve the practice of socializing value education and the role of parents in character formation of elementary school students. The community service is implemented in several action cycles that include identification of problems and needs, action planning, action implementation, monitoring, evaluation, and follow-up. Data collection was carried out through questionnaires, interviews, direct observation, and activity documentation, involving key stakeholders: teachers, parents, students, and the school. This activity demonstrates that ongoing character education outreach can increase parental awareness and responsibility in educating children at home. Parents who participated in the training and outreach modules demonstrated changes in parenting patterns, increased consistency in instilling character values ​​at home, and more open communication with the school. However, barriers such as limited time, parental educational background, and environmental and digital technology influences still need to be addressed to ensure more equitable and sustainable character change in children. The conclusion of this community service program states that early childhood character education can be more effective when implemented collaboratively between schools and parents, using a flexible and contextual approach. For sustainability, it is recommended that parent outreach and empowerment activities be conducted routinely, using materials that are relevant and adaptive to family circumstances, and that regular monitoring and evaluation be conducted. This community service program is expected to provide a foundation for more synergistic and long-term character education policies and practices.